Konsep Pendidikan Menurut al-Mawardi dalam Kitab Adab ad-Dunya wa ad-Din - Huzain, Muh. (Al-Riwayah : Jurnal Kependidikan, 2017)
Al-Mawardi in the book Adab ad-Dunya wa ad-Din said that education and efforts to educate with expression of ta’dib. The using of terms of ta’dib consistently by Al-Mawardi in his book indicates that education as a conscious, planned, and continuous effort to train and develop the potential of the human being in order to establish a behavior, morals and ethics in life and refers to the enhancement of human dignity. Al-Mawardi said that know that the human soul is always dominated by lust with inclination on something useless and bad. Therefore, in order that human behavior is good, they need education and counseling process. To achieve good behavior, human is hampered by the lust. Educational process with the dominant role of reason in human beings will shape immoral human. Know that moral behavior is formed through exercise and would be better because of habituation.